A College Course on Relativity and Cosmology - Cheng, Ta-Pei (Oxford University Press USA, 2015)
This advanced undergraduate text introduces Einstein's general theory of relativity. The topics covered include geometric formulation of special relativity, the principle of equivalence, Einstein's field equation and its spherical-symmetric solution, as well as cosmology. An emphasis is placed on physical examples and simple applications without the full tensor apparatus. It begins by examining the physics of the equivalence principle and looks at how it inspiredEinstein's idea of curved spacetime as the gravitational field. At a more mathematically accessible level, it provides a metric descr.